Barriers to Enrollment in a Pharmacist-Led Fitness, Nutrition, and Weight Management Coaching Program - Matthew J Lengel; Cathy Kuhn; Allison Wehr; Marialice Bennett; James McAuley (University of Minnesota Libraries Publishing, 2017)
Objectives: To investigate barriers to utilization of a pharmacist-led fitness, nutrition, and weight management coaching program, as well as describe patient reported expectations and explore the patient characteristics potentially associated with a higher willingness to participate in the future. Design: Cross-sectional, descriptive study using an anonymous, electronic survey. Setting: A large, national, grocery store chain. Participants: Employee benefit plan members, eligible for a pharmacist-led fitness, nutrition, and weight management (FNWM) coaching program, who were not currently or previously enrolled in the program, and met coaching program qualifications. Intervention: Peer-reviewed, electronic survey administered and collected using an Internet survey analysis software. Main Outcome Measures: Barriers to enrollment in the pharmacist-led fitness, nutrition, and weight management coaching program. Results: Of 1,130 emailed employees, 352 responded and 133 met study inclusion criteria and completed the whole survey. Of those who fit inclusion criteria, the majority (53.4%) of the respondents were aware of the coaching program (75.2%) and expressed interest in future participation (53.4%). "I am already taking steps to improve my health" and "I do not have time to participate in the program" were the highest rated barriers for both those interested and not interested in participating in the coaching program. The majority of participants believed pharmacists were qualified to provide the coaching service (78.2%) and preferred one-on-one coaching with the pharmacist (67.7%). Key topics respondents wanted the pharmacist to cover included general diet and nutrition, weight management strategies, and vitamins and supplements. Conclusion: The two major barriers reported in the study were lack of time and the use of other health improvement methods; however, a large number of respondents indicated future interest in participating. Future programs may be able to increase utilization by focusing on programming that is more accommodating to participants' schedules and integrating along with other weight loss programs. This study also provides some support regarding patient acceptance of pharmacists in innovative roles, such as fitness, nutrition, weight management coaching. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Original Research